2022
DOI: 10.1021/acs.energyfuels.1c04266
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Gas Fracturing in High Dip Angled Coal Seams for Improved Gas Drainage Efficiency at Hashatu Coal Mine

Abstract: Effective gas drainage for the gassy coal seam is a technological measure to prevent excessive gas outing and gas related mine hazards. CO2 gas fracturing (CO2-Frac) is a new technology for coal mine gas control, and its effectiveness has been proven from many coal fields across China. CO2-Frac has been successfully implemented for gas drainage in single gently inclined coal seam, but it has not been experimented in steeply inclined multicoal seam. In this study, a pilot CO2-Frac project was carried out in Has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In the CO 2 blasting experiment, a type φ89 mm fracturing pipe made by Henan Polytechnic University, , China, was used. The fracturing pipe consisted of an inflation valve, heater, fracturing tube, controlled-pressure shears, and jet valve.…”
Section: Engineering Experiments and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CO 2 blasting experiment, a type φ89 mm fracturing pipe made by Henan Polytechnic University, , China, was used. The fracturing pipe consisted of an inflation valve, heater, fracturing tube, controlled-pressure shears, and jet valve.…”
Section: Engineering Experiments and Methodsmentioning
confidence: 99%
“…CO 2 blasting is a green fracturing technology, has less impact on the formation and environment, and has the potential of mitigating global warming . CO 2 blasting is a dynamic load fracturing technique, which involves the conversion of liquid CO 2 into the gas phase to release a large amount of energy into the coal rock, thus producing a fracturing effect. Compared with high-energy gas fracturing, the dynamic load formed by CO 2 blasting has a lower frequency and longer wavelength, which can form a large fracture system in coal reservoir. CO 2 blasting has been shown to have great technical advantages in underground gas drainage in coal mines. , The influence radius of a single hole reaches 7–12 m, the permeability of the reservoir increases by 50–100 times on average, and the flow rate of the single-hole gas extraction increases by 2–8 times .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the gas is not fully discharged and operators enter the mine, the problem of gas poisoning will occur. Moreover, the gas is flammable and explosive, and reaching the ignition point under aerobic conditions will cause an explosion [12]. Therefore, it is critical to effectively discharge mine gas and reduce its concentration.…”
Section: Coal Mine Gas Control Based On Hydraulic Fracturing Technologymentioning
confidence: 99%
“…Like gas fracturing technology, it can effectively improve the permeability of coal and rock. , The introduction of this technology to China showed that CO 2 -Frac led to an increase in gas concentration in the coal mine roadway, demonstrating its potential feasibility for gas control. Over the past decade, Cao’s team conducted large-scale industrial experiments for gas control in Luan Group, Huayang Group, and other coal mining areas. These experiments involved the completion of hundreds of thousands of meters of experimental roadways, and the results revealed that the permeability of coal seams increased by 1–2 orders of magnitude, while gas extraction concentration and flow rate increased by 1 order of magnitude.…”
Section: Introductionmentioning
confidence: 99%